Is There an Association Between Whole‐body Pain With Osteoarthritis‐related Knee Pain, Pain Catastrophizing, and Mental Health?. Issue 12 (December 2015) - Dave, Amish J.; Selzer, Faith; Losina, Elena; Klara, Kristina M.; Collins, Jamie E.; Usiskin, Ilana; Band, Philip; Dalury, David F.; Iorio, Richard; Kindsfater, Kirk; Katz, Jeffrey N.
Abstract: Background: Greater levels of self‐reported pain, pain catastrophizing, and depression have been shown to be associated with persistent pain and functional limitation after surgeries such as TKA. It would be useful for clinicians to be able to measure these factors efficiently. Questions/purposes: We asked: (1) What is the association of whole‐body pain with osteoarthritis (OA)‐related knee pain, function, pain catastrophizing, and mental health? (2) What is the sensitivity and specificity for different cutoffs for body pain diagram region categories in relation to pain catastrophizing? Methods: Patients (n = 267) with knee OA undergoing elective TKA at one academic center and two community orthopaedic centers were enrolled before surgery in a prospective cohort study. Questionnaires included the WOMAC Pain and Function Scales, Pain Catastrophizing Scale (PCS), Mental Health Inventory‐5 (MHI‐5), and a pain body diagram. The diagram documents pain in 19 anatomic areas. Based on the distribution of the anatomic areas, we established six different body regions. Our analyses excluded the index (surgically treated) knee. Linear regression was used to evaluate the association between the total number of nonindex painful sites on the whole‐body pain diagram and measures of OA‐related pain and function, mental health, and pain catastrophizing. Generalized linear regression was used to evaluate the association between the number of painful nonindex body regions (categorized as 0; 1‐2; or 3‐6) with our measures of interest. All models were adjusted for age, sex, and number of comorbid conditions. The cohort included 63% females and the mean age was 66 years (SD, 9 years). With removal of the index knee, the median pain diagram score was 2 (25 th, 75 th percentiles, 1, 4) with a range of 0 to 15. The median number of painful body regions was 2 (25 th, 75 th percentiles, 1, 3). Results: After adjusting for age, sex, and number of comorbid conditions, we found modest associations between painful body region categories and mean scores for WOMAC physical function (r = 0.22, p < 0.001), WOMAC pain (r = 0.20, p = 0.001), MHI‐5 (r = −0.31, p < 0.001), and PCS (r = 0.27, p < 0.001). A nonindex body pain region score greater than 0 had 100% (95% CI, 75%‐100%) sensitivity for a pain catastrophizing score greater than 30 but a specificity of just 23% (95% CI, 18%‐29%). A score of 3 or greater had greater specificity (73%; 95% CI, 66%‐79%) but lower sensitivity (53%; 95% CI, 27%‐78%). Conclusions: We found modest associations between the number of painful sites on a whole‐body pain diagram and the number of painful body regions and measures of OA‐related pain, function, pain catastrophizing, and mental health. Patients with higher self‐reported body pain region scores might benefit from further evaluation for depression and pain catastrophizing. Level of Evidence: Level III, therapeutic study.